1997
DOI: 10.1139/y97-036
|View full text |Cite
|
Sign up to set email alerts
|

Chronic focal neocortical epileptogenesis: Does disinhibition play a role?

Abstract: Several lines of evidence have suggested that decreases in postsynaptic inhibition may have a role in epileptogenesis in cortical structures. However, other studies have suggested that GABAergic inhibition is spared, or even augmented in some forms of post-lesional epilepsy. In the studies described here, inhibitory events were recorded in two models of post-lesional chronic epileptogenesis. (i) As previously reported (D.A. Prince and G.-F. Tseng. J. Neurophysiol. 69: 1276-1291. 1993), epileptiform activity de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…The enhanced glutamatergic excitation in the cortices treated with higher concentrations of the GABA-A receptor antagonist suggests that inhibitory transmission was sufficient to partially suppress enhanced excitation. These findings concur with those of previous anatomical studies of the chronically injured cortex that show an increase in symmetrical synapses on dendritic shafts (Rutledge, 1978), and with physiological studies that show an increase in inhibitory synaptic currents in layer V pyramidal neurons (Prince et al, 1997). In contrast, a recent quantitative study on the chronically injured cortex showed an increase in the ratio between the AMPA-KA receptor-mediated excitation and GABA-A receptor-mediated inhibition (Li and Prince, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…The enhanced glutamatergic excitation in the cortices treated with higher concentrations of the GABA-A receptor antagonist suggests that inhibitory transmission was sufficient to partially suppress enhanced excitation. These findings concur with those of previous anatomical studies of the chronically injured cortex that show an increase in symmetrical synapses on dendritic shafts (Rutledge, 1978), and with physiological studies that show an increase in inhibitory synaptic currents in layer V pyramidal neurons (Prince et al, 1997). In contrast, a recent quantitative study on the chronically injured cortex showed an increase in the ratio between the AMPA-KA receptor-mediated excitation and GABA-A receptor-mediated inhibition (Li and Prince, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Traditionally, the role of inhibitory interneurons is to maintain reasonable firing frequency levels, and a shift in the balance between excitation and inhibition toward excitation is often associated with epileptic states (Dichter and Ayala, 1987;Tasker and Dudek, 1991;Galarreta and Hestrin, 1998;Nelson and Turrigiano, 1998). A number of studies conclude, however, that synaptic inhibition remains functional in many forms of paroxysmal activities (Higashima, 1988;Davenport et al, 1990;Traub et al, 1996;Esclapez et al, 1997;Prince et al, 1997;Cohen et al, 2002;Timofeev et al, 2002;Engel et al, 2003;Topolnik et al, 2003). In agreement with these findings, the role of inhibition is rather subtle in our model.…”
Section: Balanced Excitation and Inhibitionsupporting
confidence: 84%
“…In a mathematical model of layer V cortical neurons, Bush et al (1999) ''induced'' epileptiform activity by increasing pyramidal cell excitability, which was often paralleled by increased perisomatic inhibition. Increased inhibition was actually observed experimentally in postlesional epileptogenic slices (Prince et al, 1997) supporting the ''counterintuitive'' hypothesis of increased inhibition facilitating ictogenesis. This is in line with previous findings that GABA or GABA-enhancing substances can induce epileptiform activity (Kaila et al, 1997;Lopantsev and Avoli, 1998).…”
Section: Discussionsupporting
confidence: 68%